Diferential expression pattern of co-inhibitory molecules on CD4+ T cells in uncomplicated versus complicated malaria - Abel Annemieke; Steeg Christiane; Owusu-Dabo Ellis; Aminkiah Francis; Addai-Mensah Otchere...et al (Springer Nature, 2023)
This article is published by Springer Nature and is also available at https://doi.org/10.1038/s41598-018-22659-1